Etiologic factors in testicular germ cell tumors - McGlynn, Katherine A. (2009)
Globally, testicular cancer incidence is highest among men of northern European ancestry and lowest among men of Asian and African descent. Incidence rates have been increasing around the world for at least 50 years, but mortality rates, at least in developed countries, have been declining. While reasons for the decreases in mortality are related to improvements in therapeutic regimes introduced in the late 1970s, reasons for the increase in incidence are less well understood. An accumulating body of evidence suggests, however, that testicular cancer arises in fetal life. Perinatal factors, including exposure to endocrine disrupting chemicals, have been suggested to be related to risk.